The educational Evolution in Iran and Germany: the case of primary education (Grundschule) - Ashrafi, Ali (Journal of Education Culture and Society, 2019)
Aim. In recent decades, according to the enormous transformation in educational systems, the importance of educational spaces in the developed world has been increasingly sought after by educators and due to think of all the more attractive these spaces, they have thought differently. The present study was conducted to study the evolution of the educational environment of primary schools in Iran and Germany and compare them with each other.Methods. This research is descriptive research based on the comparative method. The study has also the standards criteria for designing primary schools in Iran and Germany.Results. The results of the research point to various differences between schools in Iran and Germany and then justify the differences similarities between the organization of primary education, description of the primary education system, selecting and training teacher education and similarity how to select and educate the teacher.Conclusion. The study showed In Iran, a major factor in the development of education is religion. In the pre-Islamic period, Zoroastrianism has been a factor in the philosophy and principles of education. After Islam, education has benefited from the philosophy and principles of Islam and has fully influenced primary education. But in the primary period of the German educational system, politics, ideology and the opinion of educators have played an important role in the transformation of education and, as such, in primary education.